STUDY ON FOOD SECURITY AMONG FARM HOUSEHOLDS PARTICIPATING IN THE SUSTAINABLE FOOD YARD (SFY) PROGRAM IN SEMARANG CITY - Nugraha, Fadhil Adi; Ekowati, Titik; Sumarsono; Gayatri, Siwi (Agric, 2023)
Food security in Indonesia can realized when the population’s food needs are met. One of the efforts to increase food security carried out by the Food Security Agency under the Indonesian Ministry of Agriculture is implementing the Sustainable Food Yard (SFY) program or Pekarangan Pangan Lestari (P2L) in Indonesia. The SFY program utilizes yards, idle land, or empty land for agricultural activities. Semarang City includes the regions that have received the SFY program since 2020. This research aims to determine the status of food security and the role of the SFY program on the food security of farm households participating in the SFY program in Semarang City—the research conduct using a survey method on 130 farm household samples. The data collection technique is in the form of interviews using a 24-hour food recall questionnaire. The data obtained was then processed using cross-tabulation analysis between energy sufficiency percentage and food expenditure shared with the Microsoft Excel application to determine the food security status of farm households. The role of the SFY program on the food security of participating farm households was analyzed descriptively. The research results show that the distribution of food security status of farm households participating in the SFY program in Semarang City is 88.46 percent food secure, 3.08 percent vulnerable, and 8.46 percent questionable. The role of the SFY program in the food security of farm households is not very significant in increasing energy consumption and reducing household food expenditure.